Peran orang tua dan guru dalam mengembangkan kepemimpinan pada anak usia dini - Maulidia, Arin Nafisa (Maliki Interdisciplinary Journal, 2025)
Educational leadership is the process of influencing, directing, and coordinating individuals within educational institutions to achieve educational goals effectively and efficiently, involving motivation, guidance, strategy formulation, and resource management. Effective educational leaders have a clear vision, high expectations, the ability to provide feedback, and the ability to adapt. Various leadership models are applied, such as charismatic, transactional, transformational, democratic, authoritarian, situational, etc., each with its own advantages and disadvantages. Successful leadership strategies include the development of teacher competencies, the use of technology, and collaboration with parents. Factors such as knowledge, skills, adaptation to the work environment, and personality attitudes influence the effectiveness of leadership. Leadership in early childhood plays a crucial role in creating a learning environment that supports children’s development. Teachers and parents play a crucial role in training children’s leadership skills from an early age through character education and appropriate parenting. Democratic parenting is highly recommended for the formation of good character in children. Education within the family is the foundation of the entire education system.